Participación en plusvalía en la legalización de desarrollos humanos realizados clandestinamente caso de estudio: barrio La Cecilia – sector catastral Aguas Claras 201304, localidad cuarta San Cristóbal. (Bogotá – Colombia) (2017)
At the beginning of the 20th century, Bogotá has been a center of migration for inhabitants throughout the country. As a consequence, creation of new human settlements on the periphery of the city illegally. Local authorities are not able to provide these settlements on the outskirts of the city with infrastructure, energy, drinking water and waste collection due to their clandestinely. To be legalized they must contribute with the Plusvalia’s value, which is a municipal tax charged by the town hall on properties by land uses changes and urbanistic interventions. This document analyses the situation of the participation in plusvalia’s value of the locality of San Cristobal focusing on the case study of the recently legalized neighbourhood La Cecilia. The objective of this study is to analyse the social and urbanistic impact generated by the collection of plusvalia’s value in neighbourhoods recently legalized for the city of Bogotá. The methodology used to carry out the research was the analysis of the case study of the neighbourhood La Cecilia, visiting the sector, studying the background and new documentation of the recent legalization. The results of the analysis will establish whether the participation parameters for La Cecilia neighbourhood are consistent with the reality of the sector.